Navigating Governance Asymmetry in Sustainable Infrastructure Transformation: Integration of ESG Architecture and Digitalization in Ministries of Public Works (KemenPU) and Local Governments - Ayu Purnamasari Asih; Mohamad Rizan; Muhammad Awaluddin (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
Sustainable infrastructure transformation demands the integration of Environmental, Social, and Governance (ESG) principles into public sector business strategies. The Ministry of Public Works has issued a number of centrally designed policy instruments the Building Management Information System (SIMBG), the Green Building Mandate (BGH), the Domestic Component Level (TKDN) obligations, and State Property grants to local governments but their implementation at the regional level remains uneven. This research questions how governance asymmetry between the central and regional governments affects the adoption of sustainable infrastructure standards, through what mechanisms policy instruments are distorted into administrative compliance, and what kind of governance models can position ministries as strategic orchestrators. The study uses a qualitative plural case study design based on document analysis on secondary sources available to the public, for the period 2021–2025, with four purposively selected policy cases. The evidence relies mainly on regulations, official evaluation results, and the findings of state audit bodies; data are coded deductively using the Technology Organization Environment (TOE) framework and inducively for emerging mechanisms, followed by cross case synthesis. One diagnostic pattern anchored the analysis: The 2024 National SPBE Index reached 3.12 on a scale of 5 and exceeded the medium term target, while only 48 of the 615 agencies evaluated achieved the highest predicate, an aggregate achievement that conceals a highly uneven distribution. In all four cases, the instrument establishes compliance thresholds that can be administratively verifiable but independent of substantive outputs. The resulting pattern is interpreted as means ends decoupling, with a self reinforcing form called a compliance trap, understood not as a new concept, but as a domain specific manifestation of isomorphic mimicry in ESG policy. The article proposes a tiered governance model equipped with tiering indicators, the role of actors, two way transition mechanisms, resource needs, and enforcement limits. Because the evidence base is documentary, the findings are presented as propositions that can be generalized analytically and are open to testing, rather than as a causal claim that has been validated.